ANALISIS TRAILER ANIMASI 3D TERHADAP RECALL AUDIENCE (STUDI KASUS BIOSKOP BATAM) - Putri, Weni Lestari; Jarti, Nanda (Jurnal Liga Ilmu Serantau, 2025)
This study aims to analyze the impact of 3D animated trailer displays on the audience's recall. The background of this research is driven by the importance of visual elements in attracting the audience's attention, particularly through 3D animated film trailers shown in cinemas. The research model used is descriptive quantitative, with analysis using regression and t-tests to measure the effect of 3D animated trailers on the audience's recall level. The population of this study consists of cinema visitors at Mall Batam, with an appropriate sampling technique to reflect the impact of trailer displays. The results indicate that the 3D animated trailer display has a significant effect on improving audience recall, as reflected in the increased number of visitors attending. The conclusion of this study is that 3D animated film trailers are effective in attracting the audience's attention and enhancing their recall of the film promoted in the Mall Batam cinema.